2009
DOI: 10.2214/ajr.08.2115
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Exposure to Patients During Interventional Procedures in 20 Countries: Initial IAEA Project Results

Abstract: Interventional procedures are increasing in developing countries, not only for adults but also for pediatric patients. The situation with respect to staff protection is considered generally acceptable, but this is not the case for patient protection. Many patients exceeded the dose threshold for erythema. A substantial number (62%) of percutaneous transluminal coronary angioplasty procedures performed in developing countries in this study are above the currently known dose reference level and thus could be opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(53 citation statements)
references
References 26 publications
1
51
1
Order By: Relevance
“…In this study, the 20% of IPs performed in children was larger than the figures reported in the IAEA studies, which indicated that developed countries performed 10% and developing countries 5% of IPs in children (Tsapaki et al 2009). Unlike adults, the major concern in children is minimizing the potential increase in radiation-induced cancer risks.…”
Section: Examination Frequency In Interventional Procedurescontrasting
confidence: 72%
“…In this study, the 20% of IPs performed in children was larger than the figures reported in the IAEA studies, which indicated that developed countries performed 10% and developing countries 5% of IPs in children (Tsapaki et al 2009). Unlike adults, the major concern in children is minimizing the potential increase in radiation-induced cancer risks.…”
Section: Examination Frequency In Interventional Procedurescontrasting
confidence: 72%
“…This study shows that IC procedures are increasing in developing countries, as also shown by the results of another IAEA project covering 20 countries 26. The current study, however, is focused on the Asia-Pacific region to provide a clearer picture of the situation in this part of the world.…”
Section: Discussionmentioning
confidence: 66%
“…A few studies have evaluated radiation doses in several IVR X‐ray systems 23 , 24 , 25 , 26 . To our knowledge, however, no detailed report has evaluated image quality (such as spatial resolution and low‐contrast detectability) for a large number of IVR X‐ray systems.…”
Section: Introductionmentioning
confidence: 99%